National security : a primer - Gautam, P. K. (Pradeep Kumar), 1951- (New Delhi : Knowledge World, 2004)
In the Indian context
Includes bibliographical references (p. [152]-160) and index
Keywords: National security -- India; Nuclear weapons -- India; Strategic forces -- India; India -- Military policy -- India